The Anaphase Promoting Complex Regulates Yeast Lifespan and rDNA Stability by Targeting Fob1 for Degradation. Issue 3 (1st March 2014) - Menzel, Johannes; Malo, Mackenzie E; Chan, Cynthia; Prusinkiewicz, Martin; Arnason, Terra G; Harkness, Troy A A
Abstract: Genomic stability, stress response, and nutrient signaling all play critical, evolutionarily conserved roles in lifespan determination. However, the molecular mechanisms coordinating these processes with longevity remain unresolved. Here we investigate the involvement of the yeast anaphase promoting complex (APC) in longevity. The APC governs passage through M and G1 via ubiquitin-dependent targeting of substrate proteins and is associated with cancer and premature aging when defective. Our two-hybrid screen utilizing Apc5 as bait recovered the lifespan determinant Fob1 as prey. Fob1 is unstable specifically in G1, cycles throughout the cell cycle in a manner similar to Clb2 (an APC target), and is stabilized in APC ( apc5 CA ) and proteasome ( rpn10 ∆ ) mutants. Deletion of FOB1 increased replicative lifespan (RLS) in wild type (WT), apc5 CA, and apc10 ∆ cells, and suppressed apc5 CA cell cycle progression and rDNA recombination defects. Alternatively, increased FOB1 expression decreased RLS in WT cells, but did not reduce the already short apc5 CA RLS, suggesting an epistatic interaction between apc5 CA and fob1 ∆ . Mutation to a putative L-Box (Fob1 E420V ), a Destruction Box-like motif, abolished Fob1 modifications, stabilized the protein, and increased rDNA recombination. Our work provides a mechanistic role played by the APC to promote replicative longevity and genomic stability in yeast.